Estrategias metodológicas para el desarrollo de la comprensión lectora en los niños de séptimo grado de educación básica paralelo “A” de la escuela de educación básica “García Moreno”, provincia de Chimborazo cantón Riobamba, año lectivo 2015-2016 - Guamán Cando, Jhonny Lenin (2016)
The research project was carried out at “Garcia Moreno” Basic Education School, in Riobamba city, of Chimborazo province, during the academic period 2015 with 35 students of the seventh year room “A”. After studying the problematic that affects students of this grade using the observation as a technique, it was feasible to come up methodological strategies to develop reading comprehension and checklist as an instrument. It was possible to note that students did not understand what they read through the observation. There were causes such as: they had no texts of their interest, shortcomings from lower grades. And the most important aspect they did not use adequate strategies with children of that age in order to help them to learn in a dynamic and creative environment to strengthen their understanding of texts and readings. The different methodological strategies proposed in this research were implemented based on this background and then we proceeded to use the checklist which is an instrument part of the observation technique; getting information of usual events of student allowing to know aspects such as their skills, abilities, knowledge through its application. Then the analysis and interpretation of the results obtained were positive since it was verified that the use of these strategies helps to develop the reading comprehension in the children stimulating creativity and the desire to learn reaching the proposed objective. The inductive-deductive method was used in the development of the research. It was concluded that the application of methodological strategies are important for the development of comprehension of texts and readings, knowing that understanding what we read will help us in the educational field developing the intellectual capacity and getting better everyday life way.